2016
DOI: 10.1111/vox.12368
|View full text |Cite
|
Sign up to set email alerts
|

Paired comparison of methylene blue‐ and amotosalen‐treated plasma and cryoprecipitate

Abstract: MB-cryo contained a significantly higher content of FVIII and lower content of FXIII when compared to AS-cryo, with no difference in fibrinogen activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The authors noted that the mean values for all 18 plasma protein activities tested fell within normal references ranges in all cases and that ADAMTS-13 was unaffected by either PR treatment [84]. Backholer et al reported similar findings in another paired comparison in which FV, FXI, FXIII, and fibrinogen losses were significant for MB-FFP, but not for AS-FFP, by analysis of variation (ANOVA) of FFP, MB-FFP, and AS-FFP; six other coagulation factors were unaffected by either treatment [85]. Cardigan et al noted reductions of 10% in ETP and 30% in peak thrombin in thrombin generation assays of paired MB-FFP versus FFP, but no effect on clot formation rate and a surprising 20% increase in clot firmness by ROTEM [86].…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 64%
“…The authors noted that the mean values for all 18 plasma protein activities tested fell within normal references ranges in all cases and that ADAMTS-13 was unaffected by either PR treatment [84]. Backholer et al reported similar findings in another paired comparison in which FV, FXI, FXIII, and fibrinogen losses were significant for MB-FFP, but not for AS-FFP, by analysis of variation (ANOVA) of FFP, MB-FFP, and AS-FFP; six other coagulation factors were unaffected by either treatment [85]. Cardigan et al noted reductions of 10% in ETP and 30% in peak thrombin in thrombin generation assays of paired MB-FFP versus FFP, but no effect on clot formation rate and a surprising 20% increase in clot firmness by ROTEM [86].…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 64%
“…Treatment with methylene‐blue caused a larger change to increased clot strength, compared to amotosalen‐treated or untreated plasma. Corresponding cryoprecipitate showed, although not significant for all variables, consistent decreasing clot forming potential in the order FFP, FFP(amotosalen) and FFP(methylene‐blue), expressed by longer initiation times, slower propagation rates and weaker clots . Thus, thromboelastographic assays were also helpful to quantify the impact of pathogen inactivation treatment of plasma on its overall haemostatic potential.…”
Section: Whole Blood Donations and Blood Componentsmentioning
confidence: 97%
“…The intrinsic effects of pathogen inactivation on fibrinogen structure or function are poorly understood. Backholer and colleagues published one of the first studies directly comparing the cryoprecipitate made from amotosalen‐treated plasma and cryoprecipitate made from methylene blue–treated plasma to cryoprecipitate made from untreated plasma. All cryoprecipitate in the Backholer study was made from pools of six ABO‐matched plasma units.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for an improved cryoprecipitate product with decreased risk of transfusion‐transmitted infections, rapid availability, and an extended shelf life to decrease product wastage. Numerous pathogen reduction processes, including solvent/detergent pathogen reduction technology, methylene blue plus visible light reduction technology, and amotosalen or riboflavin plus ultraviolet light technologies , have been applied to cryoprecipitate. In the past, some pathogen reduction steps in manufacturing cryoprecipitate have been reported to have a negative impact on coagulation factor activity …”
mentioning
confidence: 99%